Mesenchymal Stem Cells and Curcumin Effectively Mitigate Freund’s Adjuvant- induced Arthritis via their Anti-inflammatory and Gene Expression of COX-1, IL-6 and IL-4 - Ahmed, Rania H.; Rashad Ahmed, Rasha; Galaly, Sanaa Rida; Moustafa, Nadia; Abourehab, Mohammed A. S.; Abdelgawad, Mohamed Abdelwahab; Ahmed, Osama Mohamed; Abdul-Hamid, Manal (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background and Objectives: Rheumatoid arthritis (RA) is a type of arthritis that damages joints and can affect the thymus and the spleen. RA is an autoimmune disorder in which the immune system targets the body's own tissues. The causes of RA are unknown, although a genetic link is thought to be involved. The objective of this research was to evaluate the effect of curcumin, mesenchymal stem cells (MSCs), and their combination on the disruption of serum cytokines, ankle joint, thymus and spleen histopathology, and affected genes in complete Freund’s adjuvant (CFA)-induced arthritis in male and female Wistar rats. Methods: Experimental animals were organized into 16 groups (6 animals for each), eight groups including male rats and the other eight groups including females rats. The groups are normal control, CMC, curcumin, MSCs, CFA, CFA/curcumin, CFA/ MSCs and the arthritic group treated with MSCs and curcumin. One subcutaneous injection of 0.1 mL CFA was given to rats into the right hind leg footpad to induce RA. The arthritic rats were intravenously injected three times with bone marrow-derived MSCs (BM-MSCs) and/or treated orally with curcumin daily (100 mg per kg body weight per day) for 21 days. Results: Curcumin and BM-MSCs work together to dramatically (P < 0.05) restore the high serum PGE2 and IL-17 levels and lower the IL-13 level in arthritic rats to normal levels. Deleterious effects on the spleen and thymus histological structure were counteracted. Gene expression of COX-1 and IL-6 was increased and IL-4 was decreased; these changes were improved by the combination treatment (P < 0.05). Conclusion: Based on these findings, additive therapeutic effects on RA occur from the combined treatment of curcumin and BM-MSCs compared with their individual use (P < 0.05). Thus, it can be said that both curcumin and BM-MSCs are effective at reducing inflammation while also having beneficial effects on the ankle joint, thymus and spleen.
Keywords: Mesenchymal stem cells